Comparative analysis of the information security environment in Ukraine and Poland (survey of journalists and editors) (Communication & Society, 2022)
Information security of Ukraine and Poland with the beginning of the Russian Federation’s armed aggression against Ukraine is sensitive to various forms of information threats. Information attacks by the aggressor country accompany the challenges of the full-scale war that exploded within Eastern Europe. Active military actions on the territory of Ukraine, the migrant crisis on the border with Poland –all this tests both countries’ information environment for resilience. Journalists play an essential role in the process of information defense. In the study, we compare legal acts and governmental regulations of Ukraine and Poland in the field of information security in order to identify the current state of information security environment in both countries. In our work, we analyze the concept of “information security” in scientific studies of Ukrainian and Polish researchers, as well as in normative legal acts. Journalists and editors of leading Ukrainian and Polish media outlets were questioned about their attitudes toward existing information security doctrines and strategies. It was found that journalists of both countries (n = 46, Î±(ua)=0.75; Î±(pl)=0.78) find the tools of protection against information threats insufficient, consider the participation of journalists in the formation of information policy significant, and also consider as risky the possibility to adopt documents that would describe the social responsibility of journalists in conditions of information aggression.